Right Ventricular Angiogenesis is an Early Adaptive Response to Chronic Hypoxia‐Induced Pulmonary Hypertension. (November 2015) - Kolb, Todd M.; Peabody, Jacelyn; Baddoura, Philip; Fallica, Jon; Mock, Jason R.; Singer, Benjamin D.; D'Alessio, Franco R.; Damarla, Mahendra; Damico, Rachel L.; Hassoun, Paul M.
Abstract: Objective: Myocardial angiogenesis is presumed to play a role in RV adaptation to PH, though definitive evidence and functional correlations are lacking. We aimed to use definitive methods to correlate RV angiogenesis, hypertrophy, and function in a murine PH model. Methods: Mice were exposed to CH for 21 days to induce PH and RV remodeling. We used unbiased stereology and flow cytometry to quantify angiogenesis and myocyte hypertrophy, and pressure–volume loops to measure RV function. Results: Within seven days, RV‐specific increases in total capillary length (10, 576 ± 2574 cm vs. 6822 ± 1379 cm; p = 0.02), surface area (10 ± 3.3 cm 2 vs. 4.9 ± 1.5 cm 2 ; p = 0.01), and volume (0.0013 ± 0.0005 cm 3 vs. 0.0006 ± 0.0001 cm 3 ; p = 0.02) were observed, and RV EC proliferation increased nearly 10‐fold. Continued exposure led to progressive RVH without additional angiogenesis. RV function was preserved, but activation of hypoxia‐dependent gene expression was observed in both ventricles after 21 days. Conclusions: Early RV remodeling in CH‐PH is associated with RV angiogenesis and preserved RV function. Continued CH‐PH is associated with RVH but not angiogenesis, leading to biventricular activation of hypoxia‐dependent gene expression.